The 823rd hit - Scaletta, Kurtis. (A Topps league story, 2012)
To keep Teddy "Bear" Larrabee happy and slugging, Chad the bat boy has to figure out what a crabby fan would be willing to trade for Teddy's lucky homerun ball.